Implementing voice over Internet protocol in mobile ad hoc network – analysing its features regarding efficiency, reliability and security. Issue 5 (6th May 2014) - Sheikh, Naveed Ahmed; Malik, Ashfaq Ahmad; Mahboob, Athar; Nisa, Khairun
Abstract : Providing secure and efficient real‐time voice communication in mobile ad hoc network (MANET) environment is a challenging problem. Voice over Internet protocol (VoIP) has originally been developed over the past two decades for infrastructure‐based networks. There are strict timing constraints for acceptable quality VoIP services, in addition to registration and discovery issues in VoIP end‐points. In MANETs, ad hoc nature of networks and multi‐hop wireless environment with significant packet loss and delays present formidable challenges to the implementation. Providing a secure real‐time VoIP service on MANET is the main design objective of this paper. The authors have successfully developed a prototype system that establishes reliable and efficient VoIP communication and provides an extremely flexible method for voice communication in MANETs. The authors' cooperative mesh‐based MANET implementation can be used for rapidly deployable VoIP communication with survivable and efficient dynamic networking using open source software.